Resolva a equação incompleta:
a)a) x²+3x.(x-12)=0
Soluções para a tarefa
Respondido por
6
x²+3x (x-12)=0
x²+3x²-36x=0
4x²-36x=0
Δ=b²-4ac
Δ=(-36)²-4.4.0
Δ=1296
![x= \frac{36+-36}{8} x= \frac{36+-36}{8}](https://tex.z-dn.net/?f=x%3D++%5Cfrac%7B36%2B-36%7D%7B8%7D+)
x'=![\frac{36+36}{8} = \frac{72}{8} = 9 \frac{36+36}{8} = \frac{72}{8} = 9](https://tex.z-dn.net/?f=+%5Cfrac%7B36%2B36%7D%7B8%7D+%3D++%5Cfrac%7B72%7D%7B8%7D+%3D+9)
x''=
x²+3x²-36x=0
4x²-36x=0
Δ=b²-4ac
Δ=(-36)²-4.4.0
Δ=1296
x'=
x''=
Perguntas interessantes
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás